Acute Respiratory Distress following Intravenous Injection of an Oil-Steroid Solution - Michael Russell; Aric Storck; Martha Ainslie (Canadian Respiratory Journal)
A case of acute respiratory distress and hypoxemia following accidental intravenous injection of an oil-steroid solution in a body builder is presented. Chest roentography at the time of presentation showed diffuse bilateral opacities, and computed tomography revealed predominantly peripheral ground-glass opacifications. The patient’s symptoms gradually improved over 48 h and imaging of the chest was unremarkable one week later. The pathophysiology, diagnosis and treatment of this rare but potentially life-threatening complication of intravenous oil injection are discussed.